Distribution and abundance of euphasids off Argentina in Spring 1978 - Curtolo, Luis M; Dadon, José R; Mazzoni, Horacio E (Revista Nerítica, 2022)
Four species of euphausiids were recorded in the southwestern Atlantic off Argentina during spring 1978: Euphausia lucens, E. vallentini, Nematoscelis megalops and Thysanoessa gregaria. Ecological differences between shelf and slope environments lead to conspicuous differences in the frequency distributions of the larval stages in both water masses. A clearly differentiated environment was found in the Gulf of San Matias (41°-42°S), where E. lucens, N. megalops and T. gregaria encounter conditions which allow them to complete their life cycles without being expatriated.